Love is a four-letter word - VanSickle, Vikki (Scholastic Canada, 2011)
Clarissa Delaney has never given the word love much thought, since she is worried about her mother's illness and losing her best friend Benji to a bunch of musical theatre nerds. But when she meets Michael, everything changes